History And Development Of Sharia Accounting - Al-Anshor, Zahran Mohammad Al-Anshor; Nawadir, Miftah Maolana (JAKI : Jurnal Akuntansi, 2024)
This article was written to explain the history and development of Sharia accounting from time to time. The method used is subjective qualitative. The information obtained is from research journals and books about the history and development of sharia accounting. Sharia accounting is accounting whose recording method does not conflict with Islamic teachings. And the birth of sharia accounting goes through a long history from the time of Rasulallah SAW until it is popular today.